2012
DOI: 10.1007/s10286-012-0178-2
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime cardiac sympathetic hyper-activation in young primary insomniacs

Abstract: These preliminary findings suggest that a constant cardiac sympathetic hyper-activation throughout the night is a main feature of primary insomnia. Our evidences support the association between insomnia and increased risk for cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 32 publications
7
40
1
Order By: Relevance
“…Taken together, these findings are consistent with previous reports on the cardiac autonomic profile during nocturnal sleep in younger and older adults (Ako et al, 2003; Bonnet & Arand, 1998; Bušek, et al, 2005; de Zambotti, et al, 2014; de Zambotti et al, 2012; de Zambotti, et al, 2013; Elsenbruch, Harnish, & Orr, 1999) as well as short episodes of daytime sleep (Boudreau, et al, 2013). Collectively, these studies demonstrate an overall reduction in cardiovascular output and dominance of parasympathetic/vagal activity during NREM sleep (Busek et al, 2005), which has been associated with significant benefits for the cardiovascular system (Trinder, et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, these findings are consistent with previous reports on the cardiac autonomic profile during nocturnal sleep in younger and older adults (Ako et al, 2003; Bonnet & Arand, 1998; Bušek, et al, 2005; de Zambotti, et al, 2014; de Zambotti et al, 2012; de Zambotti, et al, 2013; Elsenbruch, Harnish, & Orr, 1999) as well as short episodes of daytime sleep (Boudreau, et al, 2013). Collectively, these studies demonstrate an overall reduction in cardiovascular output and dominance of parasympathetic/vagal activity during NREM sleep (Busek et al, 2005), which has been associated with significant benefits for the cardiovascular system (Trinder, et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Notwithstanding, our descriptive data are consistent with previous literature showing that LF power drops after sleep onset, steadily decreases across NREM sleep, and rises again during REM sleep (Bušek, et al, 2005; Trinder, et al, 2001). Likewise, the LF/HF ratio is reduced during N2 and N3 compared to wakefulness, and markedly increased during REM sleep (Burgess, Penev, Schneider, & Van Cauter, 2004), with a similar or higher ratio during REM relative to wakefulness (Bušek, et al, 2005; de Zambotti, et al, 2014; de Zambotti, et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Fifth, confounding of NSBP with other cardiovascular risk factors is possible, although multiple risk factors were adjusted in the analysis. Nonetheless, the increase in night-time BP may be a marker for deleterious factors such as orthostatic hypotension during the day [44], increased night-time sympathetic activity [45]. obstructive sleep apnea [46], or increased sodium intake [37].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, a dysregulated sleep/wake cycle may lead to greater circulating levels of pro-inflammatory biomarkers that affect hemodynamics. Indeed, case-control studies have shown that diagnosed insomnia was related to blunted nocturnal blood pressure dipping (Lanfranchi et al, 2009), impaired heart rate variability (Spiegelhalder et al, 2011), constant cardiac sympathetic hyperactivation at night (de Zambotti et al, 2013), and greater carotid intima media thickness (Nagai et al, 2013). Thus, neuroendocrine dysregulation, poor sleep behaviors, and mental health disturbances in response to childhood abuse likely lead to persistent sleep disturbances, which in turn incite an inflammatory response that affects vasculature functioning and structure.…”
Section: Discussionmentioning
confidence: 99%